ERCC4 variants identified in a cohort of patients with segmental progeroid syndromes. Issue 2 (17th November 2017) - Mori, Takayasu; Yousefzadeh, Matthew J.; Faridounnia, Maryam; Chong, Jessica X.; Hisama, Fuki M.; Hudgins, Louanne; Mercado, Gabriela; Wade, Erin A.; Barghouthy, Amira S.; Lee, Lin; Martin, George M.; Nickerson, Deborah A.; et al.
Abstract: Pathogenic variants in genes, which encode DNA repair and damage response proteins, result in a number of genomic instability syndromes with features of accelerated aging. ERCC4 ( XPF ) encodes a protein that forms a complex with ERCC1 and is required for the 5′ incision during nucleotide excision repair. ERCC4 is also FANCQ, illustrating a critical role in interstrand crosslink repair. Pathogenic variants in this gene cause xeroderma pigmentosum, XFE progeroid syndrome, Cockayne syndrome (CS), and Fanconi anemia. We performed massive parallel sequencing for 42 unsolved cases submitted to the International Registry of Werner Syndrome. Two cases, each carrying two novel heterozygous ERCC4 variants, were identified. The first case was a compound heterozygote for: c.2395C > T (p.Arg799Trp) and c.388+1164_792+795del (p.Gly130Aspfs*18). Further molecular and cellular studies indicated that the ERCC4 variants in this patient are responsible for a phenotype consistent with a variant of CS. The second case was heterozygous for two variants in cis: c.[1488A > T; c.2579C > A] (p.[Gln496His; Ala860Asp]). While the second case also had several phenotypic features of accelerated aging, we were unable to provide biological evidence supporting the pathogenic roles of the associated ERCC4 variants. Precise genetic causes and disease mechanism of the second case remains to be determined. Abstract : Segmental progeroid syndrome patients carrying novel ERCC4 variants were identified. Newly identified and previously reported ERCC4 variants are shown in A. Series of cell biological studies were performed to establish biological evidence of the pathogenicity. Conservations of three missense variants and the 3D model for the impact of p.Ala850Asp variant are shown in B and C.